An Analysis of Conceptual Metaphor in Malay Comedy Sitcoms (Jurnal Bahasa, 2025)
Comedy sitcoms incorporate humour that elicits amusement among audiences through spoken language and physical gestures. However, the humour often leads to misinterpretations, making it difficult for the audience to grasp the underlying meaning of the performance. This is because humour typically contains implied meanings and metaphors. From a cognitive linguistic perspective, conceptual metaphors serve to express abstract ideas or to elucidate complex concepts. Nevertheless, the abstract nature and complexity of such concepts often result in misinterpretation. This study analyses the conceptual metaphors used in the Malay comedy sitcom Sepahtu Reunion Live 2022 by applying the hybrid theory. Employing a qualitative content analysis approach, data were obtained via the online streaming platform Sooka TV (https://www.sookatv.com/), comprising nine episodes of Sepahtu Reunion Live 2022 aired between June 2022 and October 2022. Findings reveal that conceptual metaphors used by the performers (comedians) serve to conceptualise abstract and implicit entities in order to explain complex ideas. These include concepts of EMOTION, LOVE, AFFECTION, LIFE, DEATH, HUMAN TRAITS AND BEHAVIOURS, and MORAL VALUES. Although presented in humorous form, these complex concepts reveal the power of humour not merely as comic relief but as a medium capable of altering attitudes, perceptions, and beliefs. Ultimately, such humour has the potential to elicit meaningful and positive psychological responses.Keywords: Cognitive linguistics, metaphors, conceptual metaphor, hybrid theory, Malay comedy sitcom, Sepahtu ReunionFull text: PDF